KEMAMPUAN KANJI TINGKAT DASAR MAHASISWA PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU - Amarullah, Muhammad; Rahayu, Nana; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research was conducted to determine the basic level kanji abilities ofthe 2022 class of Japanese Language Education Study Program at Riau University. Thisresearch is qualitative research with analytical descriptive methods. The sample used in thisresearch was 37 people who were students of the class of 2022, Riau University's JapaneseLanguage Education Study Program, taken using total sampling. The results of this studyshow that the comprehension of basic level kanji for Japanese Language Education studentsat Riau University class of 2022 is classified as not good.Key words: Kanji, Kanji Comprehension, Basic Kanji